2020
DOI: 10.1111/vox.12902
|View full text |Cite
|
Sign up to set email alerts
|

Vox Sanguinis International forum on the selection and preparation of blood components for intrauterine transfusion

Abstract: The indication for IUT in our institution has to date been limited to red cell alloimmunization due to anti-D. Alpha thalassaemia and congenital infections such as Parvovirus are not uncommon in this region of the world, but the foetal and neonatal specialists in our centre have generally not advocated IUT for them. Certainly, we would not embark on an IUT programme for HbBarts that would be considered as incompatible with life. Question 2 Anti-D has been the only reason for IUT in our population. We identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Prophylactic matching of additional antigens beyond identified maternal alloantibodies is variable depending on the country, institution, and availability of RBCs. 18 Some studies found that extended matching for all IUTs was not possible for all women, but decreased alloimmunization occurred in women who received IUTs with extended prophylactic antigen matching for Fy(a), Fy(b), Jk(a), Jk(b), and S antigens. 19,20 This study is limited by its response rate (53%) and sampling method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prophylactic matching of additional antigens beyond identified maternal alloantibodies is variable depending on the country, institution, and availability of RBCs. 18 Some studies found that extended matching for all IUTs was not possible for all women, but decreased alloimmunization occurred in women who received IUTs with extended prophylactic antigen matching for Fy(a), Fy(b), Jk(a), Jk(b), and S antigens. 19,20 This study is limited by its response rate (53%) and sampling method.…”
Section: Resultsmentioning
confidence: 99%
“…This current report focuses on variability on blood component selection and processing only and addresses variability between various US institutions. 18 Despite these limitations, this study provides important data regarding contemporary transfusion medicine practices for IUTs performed in the US.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential participants were selected by the authors and the editor of the International forum series and included individuals and facilities on 5 continents (Table 1 participating countries). Ten responses were received from a range of clinical and laboratory providers serving large regional or national programmes (3 respondents) to hospital-based programmes caring for local patients (7 respondents) [2].…”
Section: Methodsmentioning
confidence: 99%